Pengaruh Penggunaan Alat Peraga Miniatur Pembangkit Energi Terbarukan listrik tenaga surya terhadap Motivasi dan Hasil Belajar Siswa SMA - Amnah, Nur (Universitas Nggusuwaru, 2025)
This study aims to determine the effect of using a miniature Solar Power Plant (PLTS) teaching aid on the motivation and learning outcomes of senior high school students in the topic of renewable energy. The research employed a quasi-experimental method with a non-equivalent control group design involving 30 students in the experimental class and 28 students in the control class. Data were collected using a learning motivation questionnaire and a multiple-choice learning outcome test. The results showed that the learning motivation of the experimental class was categorized as very high (mean 84.9), while the control class was in the high category (mean 78.2). Learning outcomes also improved significantly: the experimental class achieved a posttest mean score of 78.6 with 80% mastery, outperforming the control class with a mean of 69.3 and 46% mastery. The N-Gain score of the experimental class was 0.52 (medium category), higher than the control class which scored 0.32 (lower-medium category). Furthermore, the t-test indicated a significant difference between the two groups (t = 4.32; p = 0.000). These findings demonstrate that the use of the PLTS miniature model effectively enhances students’ motivation and learning outcomes in renewable energy topics